A Review of Trends, Research, and Recommendations for Strengthening the Evidence-Base and Quality of Residential Group Care. Issue 1 (2nd January 2016) - Boel-Studt, Shamra M.; Tobia, Lauren
ABSTRACT: Although the appropriate use of residential group care remains a subject of longstanding debate, most child welfare stakeholders, including practitioners, researchers, and advocacy groups, acknowledge that for some youth high quality group care is an essential intervention. In this article we review trends and issues related to the use of residential group care. We further review findings from outcomes research and recommendations put forth by scholars and national groups with expertise in residential care focused on building the empirical evidence-base and improving the quality of residential care for children and adolescents involved with the child welfare system.